Microscopic Infiltration of Cryopreserved Ovarian Tissue in 2 Patients With Ewing Sarcoma. Issue 3 (April 2018) - Schifflers, Stefan; Delbecque, Katty; Galant, Christine; Francotte, Nadine; Philippet, Pierre; Chantrain, Christophe F.
Abstract : We report the clinical history of 2 female patients with Ewing sarcoma and microscopic ovarian infiltration. In both cases, the initial workup found no metastasis. However, the examination of cryopreserved ovarian tissues revealed the presence of CD99 positive tumor cells with rearrangement of EWS gene confirmed by FISH. Both children were treated as patients with localized tumor and are currently in remission. These reports underline that, in Ewing sarcoma patients, retransplantation of cryopreserved ovarian tissue is not harmless and could lead to cancer relapse. These observations question also on the significance of ovarian dissemination on Ewing sarcoma prognosis and therapy.